The complete chloroplast genome sequence of strawberry (Fragaria × ananassa Duch.) and comparison with related species of Rosaceae - Cheng,Hui; Li,Jinfeng; Zhang,Hong; Cai,Binhua; Gao,Zhihong; Qiao,Yushan; Mi,Lin (PeerJ, 2017)
Compared with other members of the family Rosaceae, the chloroplast genomes of Fragaria species exhibit low variation, and this situation has limited phylogenetic analyses; thus, complete chloroplast genome sequencing of Fragaria species is needed. In this study, we sequenced the complete chloroplast genome of F. × ananassa ‘Benihoppe’ using the Illumina HiSeq 2500-PE150 platform and then performed a combination of de novo assembly and reference-guided mapping of contigs to generate complete chloroplast genome sequences. The chloroplast genome exhibits a typical quadripartite structure with a pair of inverted repeats (IRs, 25,936 bp) separated by large (LSC, 85,531 bp) and small (SSC, 18,146 bp) single-copy (SC) regions. The length of the F. × ananassa ‘Benihoppe’ chloroplast genome is 155,549 bp, representing the smallest Fragaria chloroplast genome observed to date. The genome encodes 112 unique genes, comprising 78 protein-coding genes, 30 tRNA genes and four rRNA genes. Comparative analysis of the overall nucleotide sequence identity among ten complete chloroplast genomes confirmed that for both coding and non-coding regions in Rosaceae, SC regions exhibit higher sequence variation than IRs. The Ka/Ks ratio of most genes was less than 1, suggesting that most genes are under purifying selection. Moreover, the mVISTA results also showed a high degree of conservation in genome structure, gene order and gene content in Fragaria, particularly among three octoploid strawberries which were F. × ananassa ‘Benihoppe’, F. chiloensis (GP33) and F. virginiana (O477). However, when the sequences of the coding and non-coding regions of F. × ananassa ‘Benihoppe’ were compared in detail with those of F. chiloensis (GP33) and F. virginiana (O477), a number of SNPs and InDels were revealed by MEGA 7. Six non-coding regions (trnK-matK, trnS-trnG, atpF-atpH, trnC-petN, trnT-psbD and trnP-psaJ) with a percentage of variable sites greater than 1% and no less than five parsimony-informative sites were identified and may be useful for phylogenetic analysis of the genus Fragaria.
Keywords: Fragaria × ananassa Duch.; Benihoppe; Chloroplast genome; Comparative analysis; Chloroplast DNA markers